Hepatitis E viral infection regulates estrogen signaling pathways: Inhibition of the cAMPK–PKA–CREB and PI3K–AKT–mTOR signaling pathways. Issue 6 (10th November 2020) - Gong, Shilin; Hao, Xianhui; Bi, Yanhong; Yang, Chenchen; Wang, Wenjing; Mickael, Houfack K.; Zhang, Yike; Chen, Shuangfeng; Qian, Zhongyao; Huang, Fen; Wei, Daqiao; Yu, Wenhai
Abstract: Hepatitis E virus (HEV) infection has become a global concern with high mortality rates among pregnant women, especially those in their third trimester of pregnancy. Estrogen plays an important role in mediating the body, regulating physiological and pathological processes. Estrogen is activated by binding to estrogen receptors (ERs) and mediates rapid signaling events by pathways that involve transmembrane ERs. Our previous study had confirmed that high estrogen levels during pregnancy are associated with high HEV titers. However, the association between HEV infection and estrogen signaling pathways remains unclear. In the present study, the regulation of estrogen signaling pathways by HEV infection was evaluated. Results demonstrated that HEV infection significantly inhibits the cAMP–PKA–CREB and PI3K–AKT–mTOR signaling pathways, but is independent of the Ras–Raf–MEK–ERK signaling pathway. In summary, the increasing estrogen levels and highly activated ERα during pregnancy aggravates HEV replication. The exacerbation of HEV replication, in turn, inhibits ERα expression and suppresses both cAMP–PKA–CREB and PI3K–AKT–mTOR signaling pathways. Highlights: HEV infection is an emerging global concern. Estrogen playimportant roles during pregnancy and HEV infection. HEV infection significantly inhibits the cAMP‐PKA‐CREBsignal pathway. HEV infection significantly suppresses PI3K‐AKT‐mTOR signal pathway.